Utilization of the Psoriasis Epidemiology Screening Tool (PEST): A Risk Stratification Strategy for Early Referral of Psoriatic Arthritis Patients to Minimize Irreversible Erosive Joint Damage. Issue 6 (November 2022) - Chang, Jasmine; Litvinov, Ivan V.; Ly, Christina; Netchiporouk, Elena; Tsoukas, Alexander; Thuraisingam, Thusanth; Starr, Michael; Powell, Mathieu; Christodoulou, George; Shamout, Yassein
Psoriatic arthritis (PsA) can affect a diverse range of anatomical sites and its heterogeneous presentation contributes to misdiagnosis and delayed treatment with conventional and biologic disease-modifying antirheumatic drugs (DMARDs). Up to 15% of psoriasis (PsO) patients affected by PsA remain undiagnosed. Early detection and referral to a rheumatologist are crucial to optimize care and minimize irreversible erosive joint damage. To improve the rheumatology referral process, the authors propose a risk stratification tool to identify and triage patients with possible psoriatic arthritis. With the aim of ultimately assisting in early treatment initiation, this risk stratification algorithm can be used in both dermatology and primary care clinics. It is based on the Psoriasis Epidemiology Screening Tool (PEST) combined with the ClASsification criteria for Psoriatic Arthritis (CASPAR). This article intends to provide a rationale for further prospective studies whose objective would be to validate this screening algorithm.